(untitled) (Conferencea, 2024)
Recycling waste and its use as a secondary resource have become important aspects of sustainable development and environmental protection. As people become more aware of the increasing amount of waste and environmental problems, recycling is not only economically beneficial, but also necessary for the conservation of natural resources. According to the World Health Organization (WHO), more than 2 billion tons of solid waste are generated worldwide each year. This number is growing, causing major environmental and social problems. Improper waste management pollutes soil, water, and air, and also poses a threat to human health. Therefore, waste recycling is becoming an important task for modern societies.